IMPLEMENTASI PROSES PEMBELAJARAN DEMONSTRASI UNTUK MENINGKATKAN KOMPETENSI ASUHAN PERSALINAN NORMAL PADA MATA KULIAH ASUHAN KEBIDANAN II (Studi Kasus Pada Mahasiswa Prodi D-III Kebidanan Tahun Angkatan 2011-2012 di STIKes Husada Jombang - Erieska Safitri Hendarti; Mulyoto Mulyoto; Sri Jutmini (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2016)
Demonstration Learning is learning that can reinforce theories or knowledge that has been gained by learners, thus providing an opportunity to gain the ability to better attitudes, behavior, knowledge and skills of professional basis (Nursalam, 2007). This study aims to determine (1) Implementation of the demonstrations learning process (2) Constraints and how to cope with (3) and the evaluation results to improve the demonstration learning process normal delivery care competence in the subject of Midwifery Care part 2. This study uses a qualitative method by using case study design and descriptive, which presents a complete description of a phenomenon observed in a real context. The technique of collecting data through observation, interviews, and documentation involving managers, lecturers, and students program at academic year 2011-2012 in Prodi D-III Midwifery STIKES Husada Jombang. Data were analyzed using constant comparison method by using purposive sampling technique. And in this study tested the validity of the data in a way that covers triangulation and source triangulation techniques. The results showed that learning implementation of midwifery care part 2 in STIKes Husada Jombang with enaugh effective method, because a well planned and systematic, but there are some constraints such as lack of motivation and student activity or laziness, lack of time and infrastructure. Lecturers have conducted the evaluation results in a form that is almost the same pretest and posttest. The conclusion of this study is that the achievement of student competency in normal delivery care in STIKES Husada Jombang mostly competent, but there are only few students who have the competence achievement is less, which is caused by several factors including the methods or learning strategies, instructional media and sources of learning materials.